Barzanji Tradition In Muslim Society As An Manifestation of Islamic Values Faith In the Apostles For Discipline Character - Misbahuddin Misbahuddin; Severo Espinosa III (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of the study: This research introduces a new approach to actualizing Barzanji cultural values in Islamic education, namely integrating the tradition of reading poetry and stories about the Prophet Muhammad SAW with the doctrine of faith in the apostles. This research aims to explore how islamic values are realized in the barzanji tradition. Methodology: This research uses a qualitative approach with a naturalistic research design. Data collection techniques used in-depth interviews and participant observation. Respondents in this study were selected based on variations in roles and involvement in the Ngarot tradition using purposive sampling techniques. Data analysis will be carried out using the Miles and Huberman model. Main Findings: This research also proposes suggestions and recommendations to improve and optimize this new approach, by emphasizing the importance and urgency of having a character of discipline and faith in the apostles for the success and happiness of Muslims in this world and the hereafter, based on the findings and implications. from this research. This research contributes to Islamic educational and cultural literature, by providing new perspectives and insights regarding the role and impact of Barzanji poetry and stories in increasing feelings of love, respect and gratitude for the Prophet Muhammad SAW and his predecessors, as well as asking for their intercession and blessings. Novelty/Originality of this study: Students who do not have a disciplined character and do not strengthen the value of faith in the apostles can face short-term and long-term implications for their academic, personal and social lives. Therefore, it is important and urgent for students to have a disciplined character and strengthen the value of faith in the apostles, because this is very important for their success and happiness in this world and the hereafter. Students can achieve this by studying and practicing Islamic teachings and values, as well as by reading and listening to Barzanji poetry and stories that tell the life and virtues of the Prophet Muhammad (peace be upon him) and his predecessors. In this way, students can increase their feelings of love, respect and gratitude for the Prophet and his apostles, and ask for their intercession and blessings.